2020
DOI: 10.3390/genes11080927
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of the Role of NAC Family in Flower Development and Abiotic Stress Responses in Cleistogenes songorica

Abstract: Plant-specific NAC (NAM, ATAF, CUC) transcription factor (TF) family plays important roles in biological processes such as plant growth and response to stress. Nevertheless, no information is known about NAC TFs in Cleistogenes songorica, a prominent xerophyte desert grass in northwestern China. In this study, 162 NAC genes were found from the Cleistogenes songorica genome, among which 156 C. songoricaNAC (CsNAC) genes (96.3%) were mapped onto 20 chromosomes. The phylogenetic tree constructed by CsNAC and rice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
(70 reference statements)
1
8
0
Order By: Relevance
“…About 2/3 CsDof genes are syntentic, and most paralogous gene pairs existed on different chromosomes ( Figure 2 ). The result is similar to gene families CsNAC and bZIP , and it has been reported that the expansion of bZIP and CsNAC gene families were produced by whole-genome duplication events [ 3 , 45 ]. These inferred that the expansion of the C. songorica CsDof gene family was also caused by whole-genome duplication events.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…About 2/3 CsDof genes are syntentic, and most paralogous gene pairs existed on different chromosomes ( Figure 2 ). The result is similar to gene families CsNAC and bZIP , and it has been reported that the expansion of bZIP and CsNAC gene families were produced by whole-genome duplication events [ 3 , 45 ]. These inferred that the expansion of the C. songorica CsDof gene family was also caused by whole-genome duplication events.…”
Section: Discussionsupporting
confidence: 78%
“…Gene duplication is a mechanism for gene family expansion and new gene generation. In many plants, gene family expansion is primarily involved in segmental duplication, tandem duplication, and transposition events [ 45 ]. Syntentic analysis is usually used to identify the evolutionary relationship between genes.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to their crucial function in the formation of the embryos and flowers of petunias, NAC TFs were widely studied, and multiple reports identified its key role in plant growth and development [12,13]. A large number of NAC-encoding genes have been identified and confirmed in various plants for their role in regulating wood formation [14], leaf senescence [15], fruit development [16,17], and flower morphogenesis [18,19]. Furthermore, NAC TFs also are involved in various biotic and abiotic stress responses in many plants such as Populus tomentosa [20], Arabidopsis thaliana [21], Oryza sativa [22,23], Glycine max [24], Arachis hypogaea [25], and Xanthoceras sorbifolia [26].…”
Section: Introductionmentioning
confidence: 99%
“… 38 Whole-genome analysis of the NAC gene family has been conducted in species that have been sequenced, including O. sativa , 22 Z. mays , 23 ,24 S. bicolor , 25 Triticum aestivum L., 39 Musa acuminata , 40 Vaccinium corymbosum L., 41 Juglans mandshurica , 42 Cleistogenes songorica , and Coffea canephora . 43 , 44 The identification and analysis of S. spontaneum NAC gene families at the whole-genome level have not been reported. Therefore, the purpose of this study was to study the characteristics of SsNAC genes at the genomic level and to provide a reference for further analysis of the potential function of NAC genes.…”
Section: Discussionmentioning
confidence: 99%